ANALISIS PENERAPAN MODEL PEMBELAJARAN BRAIN BALANCE LEARNING DI SEKOLAH DASAR - Ni Made Yunik Puspita Yanti; Kadek Hengki Primayana; Ni Putu Candra Prastya Dewi (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
ABSTRACT Elementary social and science learning requires learning experiences that connect conceptual understanding, active engagement, and students’ readiness to process information. In this context, Brain Balance Learning is considered relevant because it integrates multisensory activities, movement, visualization, reflection, and learning interaction, allowing cognitive functions to be engaged in a more balanced manner. This study examines how the approach has been implemented and the extent to which it contributes to social and science learning in elementary schools. The review was conducted using a Systematic Literature Review procedure guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A total of 25 national and international articles published between 2021 and 2026 were selected through identification, screening, eligibility assessment, and content synthesis. The findings indicate that 80% of the reviewed articles reported improved learning concentration, 70% documented gains in critical thinking, 55% linked the approach to increased creativity, and 45% identified strengthened scientific literacy. Student engagement was also reported in 60% of the analyzed articles. These outcomes were more evident when learning was supported by brain gym, mind mapping, visual media, animated videos, multisensory activities, and neuroscience-based e-modules. The review suggests that Brain Balance Learning can enrich elementary social and science learning by fostering active, contextual, and developmentally responsive learning experiences. ABSTRAK Pembelajaran IPAS di sekolah dasar menuntut pengalaman belajar yang mampu menghubungkan pemahaman konsep, keterlibatan aktif, dan kesiapan peserta didik dalam mengolah informasi. Dalam konteks tersebut, Brain Balance Learning dipandang relevan karena mengintegrasikan aktivitas multisensori, gerak, visualisasi, refleksi, serta interaksi belajar yang memberi ruang bagi keterlibatan fungsi kognitif secara lebih seimbang. Kajian ini menelaah bagaimana pendekatan tersebut diterapkan dan sejauh mana kontribusinya terhadap pembelajaran IPAS di sekolah dasar. Penelusuran dilakukan melalui Systematic Literature Review dengan prosedur Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Sebanyak 25 artikel nasional dan internasional yang terbit pada 2021–2026 diseleksi melalui tahap identifikasi, penyaringan, penilaian kelayakan, dan sintesis isi. Peta temuan memperlihatkan bahwa 80% artikel melaporkan peningkatan konsentrasi belajar, 70% mencatat perkembangan berpikir kritis, 55% mengaitkan penerapan pendekatan ini dengan kreativitas, dan 45% menunjukkan penguatan literasi sains. Keterlibatan belajar juga muncul pada 60% artikel yang dianalisis. Dampak tersebut lebih tampak ketika pembelajaran dipadukan dengan brain gym, mind mapping, media visual, video animasi, aktivitas multisensori, dan e-modul berbasis neurosains. Kajian ini menegaskan bahwa Brain Balance Learning berpotensi memperkaya pembelajaran IPAS melalui pengalaman belajar yang aktif, kontekstual, dan selaras dengan kebutuhan perkembangan peserta didik.